Novel Receiver Architecture for LTE-A Downlink Physical Control Format Indicator Channel with Diversity. (5th June 2014) - Abbas, S. Syed Ameer; Thiruvengadam, S. J.; Susithra, S.
Abstract : Physical control format indicator channel (PCFICH) carries the control information about the number of orthogonal frequency division multiplexing (OFDM) symbols used for transmission of control information in long term evolution-advanced (LTE-A) downlink system. In this paper, two novel low complexity receiver architectures are proposed to implement the maximum likelihood- (ML-) based algorithm which decodes the CFI value in field programmable gate array (FPGA) at user equipment (UE). The performance of the proposed architectures is analyzed in terms of the timing cycles, operational resource requirement, and resource complexity. In LTE-A, base station and UE have multiple antenna ports to provide transmit and receive diversities. The proposed architectures are implemented in Virtex-6 xc6vlx240tff1156-1 FPGA device for various antenna configurations at base station and UE. When multiple antenna ports are used at base station, transmit diversity is obtained by applying the concept of space frequency block code (SFBC). It is shown that the proposed architectures use minimum number of operational units in FPGA compared to the traditional direct method of implementation.